Screening for haematological and iron-related abnormalities in elite athletes — Analysis of 576 cases - Fallon, K. E. (Journal of Science and Medicine in Sport, 2008)
The aim of this prospective, cohort study was to determine the clinical and performance related utility of haematological and iron-related screening in elite athletes. Three hundred and three male and 273 female elite athletes underwent routine medical screening over a three-year period. In association with a standard medical consultation, a full blood count and iron-related variables were measured. Ten male athletes had a serum ferritin less than 30 ng/mL and satisfied AIS criteria for iron supplementation. In only one case was a disorder identified which was not expected following the clinical history and examination. Fifty-two female athletes had a serum ferritin less than 30 ng/mL and satisfied AIS criteria for iron supplementation. In the females, there were no instances in which a medical condition was identified which was not expected following the clinical history and examination. In both groups, clinically non-significant abnormalities were generally minor or isolated reductions in haemoglobin and/or haematocrit, and alterations in red cell parameters or single measures of iron status. Conclusion: Screening for haematological and iron-related abnormalities in athletes has a low yield. Due to the critical nature of the effects of anaemia and low serum ferritin on some aspects of performance it is reasonable to perform a haemoglobin and a serum ferritin on male and female athletes entering an elite training program. Isolated abnormalities which are close to the limits of their normal ranges and not accompanied by symptoms or signs of illness can almost certainly be ignored.